The performance of microbial anodes in municipal wastewater: Pre-grown multispecies biofilm vs. natural inocula. (December 2016) - Madjarov, Joana; Prokhorova, Anna; Messinger, Thorsten; Gescher, Johannes; Kerzenmacher, Sven
Highlights: Comparison of inoculation strategies for continuously operated microbial anodes. Inoculation with sludge or plain municipal wastewater yielded similar results. Also a pre-grown biofilm of exoelectrogens did not yield higher currents . 99% of the pre-grown biofilm was detached after 20 days of operation with wastewater. Abstract: In this study, different inoculation strategies for continuously operated microbial anodes are analyzed and compared. After 20 days of operation with municipal wastewater anodes pre-incubated with a biofilm of the exoelectrogenic species Geobacter and Shewanella showed current densities of (65 ± 8) μA/cm 2 . This is comparable to the current densities of non-inoculated anodes and anodes inoculated with sewage sludge. Analysis of the barcoded pre-grown multispecies biofilms reveal that 99% of the original biofilm was detached after 20 days of operation with municipal wastewater. This is in contrast to previous experiments where a pre-grown biofilm of exoelectrogens was operated in batch mode. To implement pre-grown biofilms in continuous systems it will thus be necessary to reveal a window of process parameters in which typical exoelectrogenic microorganisms including model organisms can be kept and/or enriched on anodes.